Investigation of chromosome 2q in osteoarthritis of the hand: no significant linkage in a Tasmanian population. Issue 12 (1st December 2002) - Stankovich, J; Sale, M M; Cooley, H M; Bahlo, M; Reilly, A; Dickinson, J L; Jones, G
Abstract : Background: Previous studies have suggested a strong genetic component to osteoarthritis (OA), especially that of the hand, and three linkage studies have suggested the existence of susceptibility loci in disparate regions of chromosome 2q. Objective: To examine for linkage to 2q in a Tasmanian population of women and men with familial hand OA. Methods: Hand OA (distal interphalangeal, carpometacarpal, and Heberden's nodes) was assessed by a combination of hand photographs and radiographs. A non-parametric linkage (NPL) analysis was performed on chromosome 2q of 69 members in 22 families with severe distal interphalangeal joint OA using Genehunter. A quantitative trait linkage analysis of a larger group of 456 members in 68 families was also performed using SOLAR. Results: The maximum non-parametric linkage score was 1.05 (p=0.15) at marker IL1R1, close to the centromere. All components of hand OA scores had significant heritability in this dataset (28%–35%, all p<0.001). Despite this, the quantitative trait analysis (after adjustment for age and, where appropriate, sex) yielded maximum LOD scores of 0.90 for Heberden's nodes (both sexes combined), and 1.19 for carpometacarpal OA score (women only). Conclusions: These results do not provide confirmation of linkage on chromosome 2q in the larger white population with hand OA. They suggest that there are regional variations in the genetic cause of hand OA and that other loci not on 2q may be important in this disease.